Lords of the sky fighter pilots and air combat, from the Red Baron to the F-16 - Hampton, Dan (Morrow, 2014)
"By the New York Times bestselling author of Viper Pilot, former USAF F-16 legend Dan Hampton tells the thrilling story of how fighter pilots have ruled the skies for 100 years, from the Red Baron to today's supersonic jets"..